1983
DOI: 10.1017/s0043174500068788
|View full text |Cite
|
Sign up to set email alerts
|

Solarization for Weed Control

Abstract: Solarization is a method of heating moist soil by covering it with plastic sheets to trap solar radiation. In field experiments in Israel during the summer, maximum soil temperature under plastic cover at the 5-cm depth averaged 46 to 49C. No weeds emerged under the plastic cover during solarization and weed emergence was reduced after its removal. The heating effect from solarization decreased with soil depth. Concentration of O2 in soil under plastic was similar to that in uncovered controls, but the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
0
15

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 11 publications
8
103
0
15
Order By: Relevance
“…In solarized plots mean temperature at 10 cm soil depth was observed to be 11.5 °C higher than in nonsolarized plots. This increase in soil temperature in solarized plots was normal, as has also been reported by other workers from Israel (Horowitz et al, 1983;Jacobsohn et al, 1980;Katan, 1981), California (Pullman et a1.,1981), Canada (Lazarovits et al, 1991), Mexico (Stapleton et al, 1985;Stapleton, 1991) and Pakistan (Zaki and Ghaffar, 1989). We observed that variation in temperature at different soil depths was greatly influenced by weather conditions (cloudy, sunny, rainy days with different air temperature and humidity).…”
Section: Discussionsupporting
confidence: 86%
“…In solarized plots mean temperature at 10 cm soil depth was observed to be 11.5 °C higher than in nonsolarized plots. This increase in soil temperature in solarized plots was normal, as has also been reported by other workers from Israel (Horowitz et al, 1983;Jacobsohn et al, 1980;Katan, 1981), California (Pullman et a1.,1981), Canada (Lazarovits et al, 1991), Mexico (Stapleton et al, 1985;Stapleton, 1991) and Pakistan (Zaki and Ghaffar, 1989). We observed that variation in temperature at different soil depths was greatly influenced by weather conditions (cloudy, sunny, rainy days with different air temperature and humidity).…”
Section: Discussionsupporting
confidence: 86%
“…Several viability tests conducted in one experiment to verify this hypothesis (data not presented) repeatedly showed that the Striga seeds were killed by the hot humid (polythene) condition. Similar effects of solar heating (solarization) were observed for many soilborne pests (Chauhan et al, 1988;Horowitz et al, 1983;Jacobsohn et al, 1980;Katan, 1981). It appears that under such a situation, the time needed for germination induction is shortened, probably due to a rapid activation of some respiratory enzymes or mobilization of reserve foods which may be exhausted in time, thus rendering the seed non-viable (Kust, 1963;Vallance, 1951).…”
Section: Discussionmentioning
confidence: 74%
“…la) and the soil was always wet because water vapor that evaporated was trapped by the polythene cover and was again precipitated on the soil surface. Higher soil moisture increases soil heat conductivity and seed sensitivity to high temperatures (Horowitz et al, 1983). Kust (1963) reported that prolonged storage of Striga seeds under hot humid conditions, similar to those observed under the polythene, killed the seeds.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The most effective way to manage weeds is to manage the seedbank, removing the source of competition and reducing the need for future vegetation management and disturbance (Horowitz et al 1983; Elmore et al 1997; Swanton & Booth 2004). Methods of seedbank control include continuously mowing or disking annual grasses, but several seasons are usually required, and both timing and diligence are important factors (DiTomaso 2000; Huhta et al 2001; Wilson & Clark 2001).…”
Section: Introductionmentioning
confidence: 99%